A Multi-Criteria Decision Model for Architecturing Competence in Human Performance Technology - (:unkn) unknown (ATLANTIS PRESS, 2010)
In a continuously changing environment, like globalization, technological innovation, restructuring and outsourcing, organizations can no longer cope without continually developing their competencies and human resources. As a result academic research and company practices have actively started to develop decision making models in operation and practices to meet toughening competence demands that, moreover, need to be developed at an ever faster pace. In this research paper, we bring together several processes and components in order to provide a comprehensive overview in search for conceptual representations designed to support and develop organizational competence mapping at the individual and organizational level. According to recent research, as a decision making tool Analytic Network Process (ANP) methodology may mitigate the elusiveness of the architecturing competence concept by assisting to determine the importance of criteria and selecting the best alternative between competency models.
Keywords: Human Performance Technology; Architecture of Competence; MCDM; Analytic Network Process; CORE COMPETENCES; SELECTION; INDUSTRY; SUCCESS; SYSTEMS